Correlative AFM and Scanning Microlens Microscopy for Time‐Efficient Multiscale Imaging. Issue 12 (27th February 2022) - Zhang, Tianyao; Yu, Haibo; Shi, Jialin; Wang, Xiaoduo; Luo, Hao; Lin, Daojing; Liu, Zhu; Su, Chanmin; Wang, Yuechao; Liu, Lianqing
Abstract: With the rapid evolution of microelectronics and nanofabrication technologies, the feature sizes of large‐scale integrated circuits continue to move toward the nanoscale. There is a strong need to improve the quality and efficiency of integrated circuit inspection, but it remains a great challenge to provide both rapid imaging and circuit node‐level high‐resolution images simultaneously using a conventional microscope. This paper proposes a nondestructive, high‐throughput, multiscale correlation imaging method that combines atomic force microscopy (AFM) with microlens‐based scanning optical microscopy. In this method, a microlens is coupled to the end of the AFM cantilever and the sample‐facing side of the microlens contains a focused ion beam deposited tip which serves as the AFM scanning probe. The introduction of a microlens improves the imaging resolution of the AFM optical system, providing a 3–4× increase in optical imaging magnification while the scanning imaging throughput is improved ≈8×. The proposed method bridges the resolution gap between traditional optical imaging and AFM, achieves cross‐scale rapid imaging with micrometer to nanometer resolution, and improves the efficiency of AFM‐based large‐scale imaging and detection. Simultaneously, nanoscale‐level correlation between the acquired optical image and structure information is enabled by the method, providing a powerful tool for semiconductor device inspection. Abstract : A nondestructive, high‐throughput, multiscale correlation imaging method that combines atomic force microscopy with silica microlens‐based scanning optical microscope is presented. The proposed method effectively bridges the resolution gap between traditional optical imaging and atomic force microscopy (AFM), achieves cross‐scale rapid imaging with micrometer to nanometer resolution, and improves the efficiency of AFM‐based large‐scale imaging and detection.